2017
DOI: 10.1108/pr-12-2015-0309
|View full text |Cite
|
Sign up to set email alerts
|

The joint effects of promotion and prevention focus on performance, exhaustion and sickness absence among managers and non-managers

Abstract: Purpose The purpose of this paper is to examine the main and interaction effects of self-rated promotion and prevention regulatory focus on self-rated work performance, emotional exhaustion and sickness absence for managers and non-managers separately. The authors expected that promotion focus relates positively to performance and negatively to sickness absence, while prevention focus relates positively to exhaustion and sickness absence, both for managers and non-managers. Furthermore, the authors expected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…decreasing demands) but to do so in a way that is constructive and compensates for the potential shortcomings of avoidance behaviors (e.g., by crafting challenges and resources). Because our study uses self‐reports, and in order to help respondents use less subjective frames of references (Petrou et al, 2017), work performance was assessed in comparison to (a) others (other‐reference), and (b) to one’s own past (past‐reference).…”
Section: Introductionmentioning
confidence: 99%
“…decreasing demands) but to do so in a way that is constructive and compensates for the potential shortcomings of avoidance behaviors (e.g., by crafting challenges and resources). Because our study uses self‐reports, and in order to help respondents use less subjective frames of references (Petrou et al, 2017), work performance was assessed in comparison to (a) others (other‐reference), and (b) to one’s own past (past‐reference).…”
Section: Introductionmentioning
confidence: 99%
“…Promotion focus and prevention focus have rarely been tested as simultaneous predictors by organizational research. In a few exceptions, though, empirical research has revealed that the combination of high promotion and low prevention focus benefits leader performance (Petrou et al, 2017), and also employee performance, especially when employees face challenges (Byron, Peterson, Zhang, & LePine, 2018). Therefore, in order to achieve performance on complex tasks, employees need to make choices and to clearly favour a promotion over a prevention approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, Van Zyl et al 2010found that a large portion of their sample reported to be in managerial positions; a role which is neither an inherent part of an industrial psychologist's training nor a fundamental part of his specialist skill set. A managerial role is characterised by having responsibility and authority to manage the workrelated functioning of employees (Petrou, Van den Heuvel, & Schaufeli, 2017). Non-managerial roles can be defined as specialist roles that require particular experience, expert knowledge and skills (Field et al, 2018).…”
Section: Managerial Versus Specialist Roles and Mental Healthmentioning
confidence: 99%